Thyroid Malignancy in Long Standing Multinodular Goitre: A Case Series with Review of Literature - Makde, Manjiri M; Kamal, Meherbano M; Chhadi, Tulsi S; Sathawane, Prajakta R. (Annals of Pathology and Laboratory Medicine, 2020)
Clinical presentation of patients with multinodular goitre is variable. Fine-needle aspiration (FNA) has been widely accepted as an initial step in the management of thyroid nodules. However, the usefulness of FNA to assess the risk of malignancy in thyroid nodules occurring within a long standing multinodular goitre (MNG) has not been completely clarified. Moreover, an unresolved issue is whether MNG is significantly associated with malignancy. MNG had been traditionally thought to be at a low risk for malignancy as compared to a solitary thyroid nodule (STN). However, review of literature showed no statistical difference in incidence of malignancy in both MNG and solitary nodular goitre. The incidence of malignancy in multinodular goitres has been found to vary from 7.5% to 17%. The duration of the associated goitre varies and ranges from the shortest of one month to the longest of more than 20 years. Considering this background, we are reporting a series of three cases of thyroid malignancies diagnosed on FNAC in patients having long standing goitre.